The Relevance of Amali Sufism and Philosophical Sufism in Modern Times - Elfando, Mario Excel; Nurwahidin, Nurwahidin (Pascasarjana IAIN Metro, 2023)
In modern times there has been a humanistic decadence because humans have lost direct knowledge about the authenticity of themselves and due to the ego that humans have. This creates a spiritual crisis that grips the human mind and leads to various problems. The religion of Islam has all the things that are necessary for spiritual realisation and human inner peace. Sufism, which is the contemplative way of Islam, is a means to achieve that goal. This article will discuss what are the shortcomings of modernity that need to be filled by sufism and how is the relevance of sufism, especially in its two forms, namely practical and philosophical sufism, in modern times. The purpose of this article is to find out how far practical sufism and philosophical sufism can play a role in filling the void of modernity. By using a literature study, it was concluded that sufism plays roles in overcoming the negative impacts caused by a lack of contemplative attitudes in economic, political,and social life, as well as interactions with the natural environment. Both practical and philosophical sufism are relevant to modern times. Practical sufism has a role to improve morality, while philosophical sufism has a role to enrich intellectual treasures in modern times.